ROLE OF VIRECHANA KARMA IN THE MANAGEMENT OF STHOULYA (International Journal of Ayurveda and Pharma Research, 2016)
Obesity is one of the most common, yet among the most neglected, public health problems in both developed and developing countries. In rich countries, obesity is more common among the less educated, but in poor countries, obesity is more common among the highly educated. Globally one in six adults is obese and nearly 2.8 million individuals die each year due to overweight or obesity.Recent studies using Indian specific criteria for overweight (BMI > 23), obesity (BMI > 25), and abdominal obesity (WC > 90 cm in men and >80 cm in women) have found the prevalence rates among Asian Indians exceeding those in the US population.The age-standardized prevalence of generalized obesity in South India was 46% (women: 47%; men: 43%) compared to 35% in the US.In classics Sthoulya (Obesity) mentioned under the Santarpanajanya vikarand in Bahudoshavastha condition.Different Shodhan modalities have been mentioned like Vamana, Virechana, Basti etc for Sthoulya.Hence here an attempt was made to assess the role of Virechana Karma in Sthoulya. It was an open randomized clinical study with Pre test and Post test designs, where minimum of 20 patients suffering from obesity were selected randomly. There were highly significant changes seen in parameters like BMI, Weight, Circumferences of chest, abdomen, waist, hip, & mid thigh, while significant changes seen in Mid Arm Circumferences.